Efficacy of different dipeptidyl peptidase-4 (DPP-4) inhibitors on metabolic parameters in patients with type 2 diabetes undergoing dialysis. Issue 32 (August 2016) - Park, Se Hee; Nam, Joo Young; Han, Eugene; Lee, Yong-ho; Lee, Byung-Wan; Kim, Beom Seok; Cha, Bong-Soo; Kim, Chul Sik; Kang, Eun Seok
Abstract : Abstract: Hyperglycemia is associated with increased mortality and morbidity in patients with type 2 diabetes mellitus (T2DM) who are undergoing dialysis. Although dipeptidyl peptidase-4 (DPP-4) inhibitors have been widely used in end-stage renal disease (ESRD) patients with T2DM, there are few studies on their efficacy in this population. We studied the effect of 3 different DPP-4 inhibitors on metabolic parameters in ESRD patients with T2DM. Two hundred ESRD patients with T2DM who were treated with DPP-4 inhibitors (sitagliptin, vildagliptin, or linagliptin) were enrolled and analyzed retrospectively. The changes in glycated hemoglobin (HbA1c), fasting plasma glucose, and lipid profiles were assessed before and after 3 months of treatment with DPP-4 inhibitors. Subgroup analysis was done for each hemodialysis (HD) and peritoneal dialysis (PD) group. There was no significant difference in the decrease in the HbA1c level among sitagliptin, vildagliptin, and linagliptin treatment groups (−0.74 ± 1.57, −0.39 ± 1.45, and −0.08 ± 1.40, respectively, P = 0.076). The changes in fasting blood glucose and lipid profiles were also not significantly different. In HD patients (n = 115), there was no difference in the HbA1c level among the 3 groups. In contrast, in PD patients (n = 85), HbA1c was reduced more after 3 months of treatment with sitagliptin compared with vildagliptin and linagliptin (−1.58 ± 0.95, −0.46 ± 0.98, −0.04 ± 1.22, respectively, P = 0.001). There was no significant difference in the glucose-lowering effect between the different DPP-4 inhibitors tested in ESRD patients. In PD patients, sitagliptin tends to lower the HbA1c level more than the other inhibitors. The glucose-lowering efficacy of the 3 DPP-4 inhibitors was comparable. Abstract : Supplemental Digital Content is available in the text